Status Kewarganegaraan Anak dalam Perkawinan Campuran : Analisis UU Perkawinan dan UU Kewarganegaraan - Neysa Brillian Abida; Nasywa Syifa (Jurnal Pendidikan dan Kewarganegara Indonesia, 2025)
Marriages between Indonesian citizens and foreign nationals present complex legal challenges, particularly regarding the citizenship status of children born within such unions. This research explores the legal tension between Indonesia’s Marriage Law No. 1 of 1974 and Citizenship Law No. 12 of 2006, which adopt different approaches to the inheritance of nationality and the safeguarding of children’s rights. Employing a normative juridical method, the study examines statutory regulations, judicial rulings, and scholarly legal works, supported by a comparative analysis of practices in other jurisdictions. The results demonstrate that although the 2006 Citizenship Law introduced the notion of limited dual citizenship for minors, the family unity principle maintained in the Marriage Law creates procedural ambiguities especially in matters of registration and the age threshold for citizenship determination. Such inconsistencies often give rise to administrative barriers that may place children at risk of statelessness. The study argues that aligning the two legal frameworks is imperative to achieve legal certainty and uphold the best interests of the child, consistent with international conventions ratified by Indonesia. It further suggests amending overlapping provisions and improving administrative mechanisms to ensure more coherent and effective citizenship protection for children of mixed marriages.